PENGARUH KEMAMPUAN KOMUNIKASI DAN DISPOSISI MATEMATIS SISWA SMP - Putri, Mega Sugondo; Hidayat, Wahyu; Maya, Rippi (IKIP Siliwangi, 2018)
This study aims to analyze in depth the influence of mathematical disposition on mathematical communication ability of junior high school students. The method in this research using a correlational method with quantitative approach. The population of this study is all junior high school students in one of the SMP Negeri in West Bandung amounted to 34 students. Instruments in this study using the test of mathematical communication skills as much as 5 items and the scale of mathematical disposition as much as 23 points of statement scale. The result of this research is student's mathematical disposition influenced by 76,5% then its rest influenced by other factors outside mathematical disposition equal to 23,5%.